Implementation of RFID Technology for an Efficient Student Attendance and Presence Management System at STMIK TIME Campus - Pratama Abraham Hutabarat; Pribadi, Octara; Hendri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In today’s digital era, achieving efficiency and accuracy in recording student attendance has become a significant challenge in higher education. The manual attendance system still used at STMIK TIME has proven to be inefficient, prone to fraud, and complicates the recap process. This study aims to design and implement an automated attendance system based on RFID (Radio Frequency Identification) technology to enhance the efficiency, accuracy, and transparency of student attendance. The system utilizes the ESP32 module as the main controller, the RC522 RFID reader to read student card UIDs, and a MySQL database integrated with a PHP-based website interface. The implementation results show that the system is capable of recording attendance in real-time, reducing manual errors, and minimizing proxy attendance practices. The testing process covers UID validation, database connection, RFID reading range, and system speed. This system is expected to serve as an effective solution for educational institutions to improve the quality of academic services and digitally manage student attendance.